PERAN DAN FUNGSI RUANG TERBUKA HIJAU RANTAU BARU DI KOTA RANTAU KABUPATEN TAPIN - Isma Sari; Taufik Hidayat; Danang Biyatmoko; Suyanto Suyanto (Universitas Lambung Mangkurat, 2019)
Declining quality and open public spaces, consisting of green open spaces and non-green open spaces, have improved environmental quality such as frequent flooding, increased air, and social crime and increasing social societies increasing the pressure of limited space available for social communities. Green Open Space of Rantau Baru in Rantau City is owned by Tapin Regency located in the center of Rantau City. Having facilities in the form of an artificial lake as a zone that is the main attraction of visitors is equipped with facilities, infrastructure, and urban facilities. The purpose of writing this particular problem is to find out the function and role of the existence of the New Overseas Green Space for the community. This research was written based on literature review and secondary data related to the existence of a new Green Rantau Open Space, both from identification surveys, RTBL, reports, books and other scientific articles. Rantau Baru Green Open Space can provide benefits for the sustainability of ecological and social functions for urban communities. Development of the Rantau Baru Green Open Space as a green open space in urban areas. Many benefits can be felt by the community with the existence of the New Rantau Green Open Space, among others as a place for plant conservation, environmental education, sports and as a recreational destination with family.